CORRELATION BETWEEN HISTORY OF MATERNAL ANEMIA AND PREVALENCE OF 0-5 YEARS OLD STUNTING CHILDREN IN CILEMBU VILLAGE, SUMEDANG REGENCY, 2019 - Sirait, Batara Imanuel; Suryanegara, Wiradi (International Journal of Research -GRANTHAALAYAH, 2021)
Stunting is a health problem among children in Indonesia, reaching 30,8% and 29,9% on infants less than five years old and two years old. West Java prevalence of stunting is higher than 38,8% of the entire stunting population in Indonesia in 2018. ranks second in districts with the highest prevalence of stunting in West Java, which is 19,4%, according to in 2013. Stunting caused major problems are delayed mental development, lack of intellectual ability and long-term consequences of degenerative diseases. is a public health problem that burdens developed and developing countries, especially adolescents and pregnant women. Risked data reaches 48.9% of incidence on pregnant women. Maternal can increase the prevalence of stunting. The purpose of this study to determine the Correlation between the History of Maternal Anemia and Prevalence of 0-5 Years Old Stunting Children in Cilembu Village, Sumedang Regency, January 2019 Period. This study used a cross-sectional analysis method, a sample of 61 consisted of stunting children aged 0-5 years in Columbus Village. Statistics is tested by Pearson correlation and also analysis of demographic data. The prevalence of maternal 50,8%, and the highest category of stunting is very short (46%). The results of Pearson’s analysis found (p= 0.717 > 0.05) that do not have an association between the History of Maternal Anemia and the incidence of stunting aged 0-5 years old. There is no correlation between the History of Maternal Anemia and the incidence of stunting aged 0-5 years old in Cilembu Village, Sumedang Regency, January 2019 Period.